CHARACTERIZATION, CELL PROLIFERATION AND CYTOTOXICITY EVALUATION OF VASCULAR ENDOTHELIAL GROWTH FACTOR LOADED POLY (LACTIC-CO-GLYCOLIC ACID) MICROSPHERES - (:unkn) unknown (NOBEL ILAC, 2012)
Objective: The aim of this study was to encapsulate vascular endothelial growth factor (VEGF) in poly(lactic-co-glycolic acid) (PLGA) microspheres using a water-in-oil-in-water emulsification method. Particle size distribution and surface morphology of PLGA microspheres and VEGF loaded PLGA microspheres were investigated. The effect of VEGF in free form and VEGF loaded in PLGA microspheres were also evaluated in the cell culture for cell proliferation and cytotoxicity. Material and Method: Particles were sized by laser diffractometry. In vitro release profiles of VEGF from the microspheres were investigated in pH 7.4 phosphate buffer The VEGF release was assessed using the enzyme linked immunosorbant assay (ELISA). The surface morphology of the microspheres was determined by a scanning electron microscobe. For the evaluation of the cytotoxicity of the formulations and proliferation effect of VEGF, the tetrazolium dye assay (MTT test) was performed. Results: The microspheres were found to be spherical with particle size ranges of 8-12 mu m for PLGA microspheres and 8-159 mu m. for VEGF loaded PLGA microspheres and the in vitro release results indicated that VEGF was released from the microspheres up to 30 days. According to the cell culture results, the formulations were non-cytotoxic and helps cells proliferate. Conclusion: VEGF loaded microspheres were successfully prepared and their physical properties and in vitro release rate and cytotoxicity tests showed that the microspheres could be used for further in vivo experiments regarding nerve graft prefabrication.
Keywords: VEGF; PLGA; microspheres; controlled release; cell proliferation; cytotoxicity; IN-VITRO; SOLVENT EVAPORATION; RELEASE; MICROENCAPSULATION; STABILITY; DELIVERY; SURVIVAL; PEPTIDE; VEGF